A Comparative Good Governance Experiences on Local Governments Cope with COVID-19: A Case Studies Between Indonesia and Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: This article aimed to analyzed and compared good governance experiences on local government cope with Covid-19 between Indonesia and Thailand. The methodology of this article was a qualitative approach based on the secondary data from case of local government of Indonesia in Tegal City and Thailand in Chang Puak Sub-district. The finding of this article was in Indonesia case could argued that the effectiveness, openness, and transparency of the government in coping with Covid-19 are the keys to improve the people economy in Tegal City. Also, the administrators Government of Tegal should be responsive to evaluate ineffective methods in preventing the spread of Covid-19 and switch to more effective and efficient ways. In the meantime, in Thailand case, sorely local government could not cope with Covid-19 pandemic, but the cooperated between Thailand Village Health Volunteer and local government were the best operation to stop the Covid-19 outbreak. Moreover, the most foremost hinder in both Thailand and Indonesia were the central government that centralize authority. In Indonesia, the central policy was the obstacle to allow local government acted, while in Thailand the emergency decree was the main hinder for local government management. Finally, both local government in Thailand and Indonesia were struggled and tried to cope with Covid-19 in a right way of good governance track even though they had a limited authority and willing to support their community.